2000
DOI: 10.1046/j.1365-2044.2000.01472.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intrathecal ketamine added to bupivacaine for spinal anaesthesia

Abstract: We prospectively studied 30 healthy female patients undergoing intracavitory brachytherapy applicator insertion for carcinoma of the cervix under spinal anaesthesia. Patients were randomly allocated to receive either intrathecal bupivacaine 10 mg alone or bupivacaine 7.5 mg combined with preservative-free ketamine 25 mg. Spinal block onset, maximum sensory level, duration of blockade, haemodynamic variables, postoperative analgesic requirements and adverse events were recorded. Onset of sensory and motor block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
2
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 50 publications
5
59
2
3
Order By: Relevance
“…All the patients in both group attained Bromage grade 3. Our result is comparable with those of TM Krishna et al (2008), Kathirvel et al (2000) and Bharti N et al (2003). Duration of motor block in our study was in consonance with that of TM Krishna et al (2008) who also showed prolongation of motor block in midazolam-ketamine-bupivacaine group as compared to ketamine-bupivacaine group.…”
Section: Observations and Results Table 1: Demographic Datasupporting
confidence: 92%
See 3 more Smart Citations
“…All the patients in both group attained Bromage grade 3. Our result is comparable with those of TM Krishna et al (2008), Kathirvel et al (2000) and Bharti N et al (2003). Duration of motor block in our study was in consonance with that of TM Krishna et al (2008) who also showed prolongation of motor block in midazolam-ketamine-bupivacaine group as compared to ketamine-bupivacaine group.…”
Section: Observations and Results Table 1: Demographic Datasupporting
confidence: 92%
“…N Bharti et al (2003) showed that changes in blood pressure and pulse rate were comparable between midazolambupivacaine and bupivacaine alone group. Kathirvel et al (2000) also showed that patients in ketamine-bupivacaine group had significantly higher systolic and diastolic blood pressure after induction of spinal anaesthesia and also volume of intravenous fluid required to maintain blood pressure was lower in ketamine-bupivacaine group. Kaliyani et al (2001) in their study also showed that intrathecally administered ketamine caused dose dependent mild increase in pulse rate and systolic blood pressure.…”
Section: Observations and Results Table 1: Demographic Datamentioning
confidence: 84%
See 2 more Smart Citations
“…However, they provide a very limited postoperative duration of action. In order to overcome this problem and to maximise the duration of analgesia, many adjuvants, for example opioids 4 , neostigmine 4 , ketamine 5 and clonidine 6 ,have been tried increasingly in the last two decades to relieve postoperative pain. However, side-effects in the postoperative period such as nausea, vomiting, pruritus, urinary retention and respiratory depression, render most adjuvants as less than ideal.…”
Section: Discussionmentioning
confidence: 99%